Who lends to Africa and how? Introducing the Africa Debt Database - David Mihalyi; Christoph Trebesch (Kiel Institute for the World Economy (IfW Kiel), 2023)
Africa's sovereign debt markets are not well understood, partly due to a lack of data. This paper introduces the Africa Debt Database (ADD), the most granular and comprehensive dataset on external borrowing by African governments thus far. Our project moves beyond existing aggregate datasets and instead releases information on individual loans and bonds, in particular on the financial terms of each instrument. Taken together, we cover over 7000 loans and bonds between 2000 and 2020, with a total volume of 790 billion USD. Using this data, we study Africa's record lending boom of the 2010s in detail. The debt boom was mainly driven by large sovereign bond issuances in London and New York, as well as growing lending by Chinese state-owned banks. The micro data also reveal a large variation in lending terms across countries, time, and creditors. Sovereign external bonds have interest rates of 6 percent, on average, Chinese banks charge 3 percent, and multilateral organizations just 1 percent. Strikingly, many governments in Africa simultaneously borrow large amounts from both private and official creditors, at vastly different rates. The large differences in debt servicing costs are indicative of a cross-creditor subsidy, as cheap concessional loans can be used to pay the high interest to private or Chinese creditors.
Keywords: E62; F34; H63; 330; sovereign debt; debt sustainability; debt composition; bond issuances; Chinese lending